A neonate presenting with hip septic arthritis: a rare case report - Hilmi Muhammad; Prisilla Desfiandi; Rahadyan Magetsari (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Hip septic arthritis is a serious condition that requires prompt diagnosis and treatment to prevent complications such as joint destruction, growth arrest, or the spread of infection. The incidence of septic arthritis ranges from 2 to 10 cases per 100,000 individuals per year generally. Although septic arthritis can affect people of all ages, it is more common in the elderly and infants under 5 y.o. We described a case of a 5-mo.o. child who presented with right hip swelling for ten d. The patient started acting agitated and appeared to be in a lot of discomfort whenever her right leg was moved. The patient is taken to a traditional massage therapist and gets a massage. Then, the patient's right hip began to swell, accompanied by intermittent fever and limited hip movement. The patient was hospitalized for four d due to hip dislocation and received skin traction with broad-spectrum antibiotic therapy, but no clinical improvement was observed. The patient was then referred to Dr. Sardjito General Hospital, Yogyakarta, Indonesia and underwent emergency open debridement followed by immediate IV antibiotic treatment. Traditional massage therapy can cause further musculoskeletal injury, causing the formation of hematoma or hemarthrosis and even causing the development of septic arthritis. As soon as septic arthritis is suspected, adjusted antibiotic treatment and adequate joint drainage are necessary, as this condition is an orthopedic emergency, especially in neonates. From this case can be concluded that early diagnosis and treatment of septic arthritis in newborns is very important to prevent complications. The public needs to understand the dangers of massage for musculoskeletal injuries during the acute phase.